KONSEP PENGORGANISASIAN DALAM PERSPEKTIF ISLAM - Masrur, Moh.; Akmansyah, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2020)
The activity of organizing is a very important element to create qualified and Islamic system of Islamic educational institutions. Practically, there are obstacles in actualizing due to the lack of references from Islam it self. The purpose of this study is to explore the concept of organizing in an Islamic perspective and its implications for education. This study uses the library research which is part of qualitative research. The data source is taken from the al-Qur’an, al-Hadith, classic books, research journals, and other sources relating to objects. The analysis used is descriptive analysis and content analysis. The result of the study shows that Islam has different concept of organizing than the organizational concept developed by western scientists. The characteristic of organizing in Islamic perspective is to get free from the shackle of backwardness by returning humanity to the nature of monotheism (tauhid), human value, strengthen the character of people, build the social value, egalitarian value and universality. Mean while, organizing the Islamic education can be actualized by leadership based on Islamic principles, the balance between power, authority and responsibility, task division and delegation of authority and discussion.